The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1149/1.3526597
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical Simulation of Stress Evolution in Lithium Manganese Dioxide Particles due to Coupled Phase Transition and Intercalation

Abstract: Lithium manganese dioxide particles undergo a significant volume change after transition from the cubic to the tetragonal phase. The transition may cause severe damage in cathode materials and capacity fade. This paper proposes a volume expansion and diffusion model to evaluate stresses due to phase transition. A three-dimensional finite element approach is developed to account for coupled phase transition and intercalation effects, which is applicable to arbitrary particle geometries. The study shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 46 publications
(54 reference statements)
1
103
2
Order By: Relevance
“…It is shown that the ideal solution thermodynamics assumption was applied in describing the transport of lithium ions and diffusion induced stress, and is widely used in battery modeling [12][13][14][21][22][23]. Hence, the transport of Lithium ions in active particles is described by the modified Fick's law [12,24], which includes the effect of stress on diffusion:…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the ideal solution thermodynamics assumption was applied in describing the transport of lithium ions and diffusion induced stress, and is widely used in battery modeling [12][13][14][21][22][23]. Hence, the transport of Lithium ions in active particles is described by the modified Fick's law [12,24], which includes the effect of stress on diffusion:…”
Section: Electrochemistrymentioning
confidence: 99%
“…The reason can be contributed to the longer migration paths of lithium ions from the separator. Hence, combined (1) and (3) The failure of the brittle materials is often related to the tensile stress [21]. In order to capture the failure inside the LiCoO2 cathode, the 1 st principal stresses insede the cathode were calculated.…”
Section: (D) (E) (F) (G) (H) and (I)mentioning
confidence: 99%
“…One of the critical challenges of LIBs is to enhance the mechanical stability of electrode materials. Diffusion induced stresses [8,9] and phase transition [10,11] during the operations of LIBs can cause fracture and mechanical failure. Hence, it is important to understand the stress generation in battery materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies of stress generation including diffusion induced stress and phase transitions are rare. Park et al [10] calculated the stresses with phase transition and intercalation in LiMn2O4 particles, but the geometry used in the model was simple shaped particles.…”
Section: Introductionmentioning
confidence: 99%
“…3,21,25 These studies all assumed that the particles were isolated and isotropic. Park et al 4 included the effect of phase-transformation-induced stresses in their simulations, finding the phase transformation effect to be significant. Malave et al 26 performed a similar analysis, but included the effect of anisotropic swelling with phase change, using the experimental data of Reimers and Dahn 7 .…”
mentioning
confidence: 99%